Teaching Module: Biounpoll World Kit - Mohd Amran, Siti Aishah; Abu Bakar Osman, Nur Syafira; Zainuddin, Nur Irdina Khairunnisha; Mohammad Nawawi, Norazah (Multidisciplinary Applied Research and Innovation, 2021)
Promoting community commitment to protect local biodiversity especially in our own country, Malaysia is an important goal of education for sustainable development. In order to develop the biodiversity consciousness among people, a learning kit is the way to expose them to problems and everything they need to know about biodiversity. Therefore, we invented a learning kit which was developed by an enthusiast group towards STEM education focusing on biodiversity. Our own invention learning kit is known as ‘Biounpoll World Kit’ which can help to enhance the teaching and training process about biodiversity for all levels of the community. The idea of making this project is based on our observation on the low level awareness on biodiversity though a lot of campaign has been done by the government. Biounpoll world kit connects the sufficient requirement as an educational tool for the younger generations. This kit is a combination of 3 activities which are Save Anastasia and Her Friends, Unsponges and Biodiversity Flashcard. The objective of this product is to helps in encouraging the curiosity in the students and also can be very helpful in experimental learning. The activities of Biounpoll world kit helps the users about the Introduction to biodiversity, understand the impact of pollution to aquatic animals and know the benefits of eco-friendly products. This kit also allows user to develop, experiment, think, solving and explore while learning to apply the products in their life and gaining new information about the world of biodiversity. The activities offer from this kit will help to increase the knowledge of the user about our ecological biodiversity since our ecosystems are in danger. This interesting kit has potential to be commercialized and suitable as a learning kit as there is no learning kit that offer a similar content in the market.